PEDIATRIC URINARY STONE PROFILE IN SAIFUL ANWAR HOSPITAL - Balafif, Muhammad Firas; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2025)
Objective: This study aims to provide an overview of the characteristics of age, gender, stone location, stone side, stone analysis, and management of pediatric urinary stone in the tertiary hospital. Material & Methods: This was a retrospective study done over a period of four years from January 2019 - December 2023 in our institution. The patient has undergone supporting examinations to confirm the diagnosis. Clinical data including the patient’s age, gender, stone location, stone side, stone analysis, and management were observed. Data were analyzed descriptively and using SPSS 17.0. Results: Total of 55 cases of upper and lower urinary tract stones were encountered in our study with a mean age of 11.2 years. The highest incidence was 15-18 years old (36.4%). The distribution by gender showed a higher prevalence in males (67.2%) compared female patients (32.8%). The kidney stone was the most frequent clinical presentation (36.3%). From the upper urinary tract stone, the left side becomes the predominant area (54.2%). The most common stone constituent was calcium oxalate (41.8%). The kidney stone was mostly treated with Percutaneous Nephrolithotomy (PCNL) (75.0%). Conclusion: Pediatric urinary tract stone patients in our institution are predominantly male, with a peak rate in 15- 18 years old, most commonly found in the kidney, predominantly on the left side, and the most common stone constituent was calcium oxalate. Th kidney stone is mostly treated with PCNL. Keywords: Bladder stone, pediatric urinary stone, cystolithotripsy.